2008
DOI: 10.1042/bst0361422
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermodynamics of metal-loaded transferrins: transferrin receptor 1 interactions

Abstract: Transferrin receptor 1 (R) and human serum transferrin (T) are the two main actors in iron acquisition by the cell. R binds TFe(2) (iron-loaded transferrin), which allows its internalization in the cytoplasm by endocytosis. T also forms complexes with metals other than iron. In order to follow the iron-acquisition pathway, these metals should obey at least two essential rules: (i) formation of a strong complex with T; and (ii) interaction of this complex with R. In the present paper, we propose a general mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…4) [27,68,175]. Most notably, recent research evidence shows that Al-transferrin complexes are not bound by the TfR [198][199][200] because of an incomplete open/closed form which precludes them from forming specific ionic inter-residual interactions, such as those formed by iron-transferrin and the TfR [198]. This implies that Al-transferrin transfer from the blood stream to cytoplasm may not follow the classical iron-TfR acquisition pathway.…”
Section: Fate Of Dietary Aluminum: Implications For Dysregulation Of mentioning
confidence: 99%
“…4) [27,68,175]. Most notably, recent research evidence shows that Al-transferrin complexes are not bound by the TfR [198][199][200] because of an incomplete open/closed form which precludes them from forming specific ionic inter-residual interactions, such as those formed by iron-transferrin and the TfR [198]. This implies that Al-transferrin transfer from the blood stream to cytoplasm may not follow the classical iron-TfR acquisition pathway.…”
Section: Fate Of Dietary Aluminum: Implications For Dysregulation Of mentioning
confidence: 99%
“…Transferrin has also been reported to interact with lead when present in excess (Leelakunakorn et al, 2005). In addition, when saturated by non-iron metals, transferrin could compete with iron-transferrin during its interaction with transferrin receptor 1 (Ha-Duong et al, 2008; El Hage Chahine et al, 2012). Taken together, these data suggest that metals other than iron could, by using transferrin as a Trojan horse, play a role in metal distribution within the body.…”
Section: Molecular Events and Pathways Linking Iron Metabolism To Nonmentioning
confidence: 99%
“…However, the affinity of TfR 1 for the Al-Tf complex was found to be very weak in vitro, leading Hémadi et al to caution that Al transfer from blood to cell cytoplasm may not follow the TfR-ME pathway [45]. In another report from the same laboratory Ha-Duong et al found no interaction between Al-Tf and the TfR [46]. Based on structural and physicochemical characteristics of apo-Tf, Fe-Tf, Al-Tf and the TfR (diffusion coefficient, hydrodynamic radius, capillary electrophoretic mobility, and zeta potential) and calculation of acidic amino acid residues, Sakajiri et al concluded that the driving force for the formation of a complex of metal and the TfR is the electrostatic interaction between the negative charge of the former and positive charge of the latter.…”
Section: The Mechanisms Of Brain Aluminum Up-takementioning
confidence: 99%